The Reaction Extraction Combining Crystallization for Growth of Sodium Chloride in a Spray Fluidized Bed Crystallizer - Dan Zheng; Jie Yan; Jun Chen; Zeqin Wang (Journal of Chemistry)
At present, the crystal size of sodium chloride prepared by a traditional crystallization process (such as stirred crystallization) is inhomogeneous, and it has a great quantity of fine grains in crystallizer. This work presents a novel approach for the growth of sodium chloride from supersaturated solutions by reaction-extractive crystallization in a spray fluidized bed crystallizer (SFBC), in which sodium sulfate solution is transformed into potassium chloride and sulphuric acid based on a reactive extraction-crystallization process using triisooctylamine (TOL) in n-octanol as the extraction system. This paper mainly studies the effect of operating conditions (e.g., circulation flow rate, velocity ratio of oil and aqueous phases, crystallization temperature, hydraulic residence time, and feed velocity) on the crystal size distribution (CSD) during the crystallization process of sodium chloride in a SFBC. Experimental results show that the optimum conditions are 1.0362 m/s as the best circulation flow rate, 9.5 : 8.5 as the best velocity ratio of oil and aqueous phases, 313 K as the best temperature, 4320 s as residence time, and 8 mL.min−1 as the best feed velocity. Meanwhile, the proposed extraction kinetic model about extraction rates is developed and validated against data from the SFBC. And it proves that the reactive extraction system is controlled by diffusion and chemical reaction. Analysis of the extraction kinetic model and comparison with experiments reveal that the extraction kinetic model results are in well agreement with experiments. Furthermore, the uniform and large crystals can be obtained in a spray fluidized bed crystallizer without special concentration since extraction and crystallization are carried out in the same equipment. In addition, all of the sodium chloride products prepared under the optimal conditions in SFBC show a better CSD performance than the stirred crystallization. This research demonstrates that this process enables controlling the crystal size in a rather wide range, thus further underlining the potential of this technique for applications in the crystallization industry.